Property Exhibition Decision Support System Based on Web Application - Violitta Yesmaya; Angry Ronald; Monica Hidajat (Universitas Ahmad Dahlan, 2018)
Complexity in finding property on property exhibition which consider many related constraints is quite high. Customers need to spend much time to analyse the right property to buy depends on their constraints whether salary, distance to work, facility, etc. According to the problem, this research will collect the information from customer on property exhibition to find out the constraint. Also, this research will focus on design and analyses the decision support system for property exhibition. Software development life cycle that will be used is scrum which is divided into several processes like backlog, sprints, scrum meetings, and demos. The result of this research is a web application that help customer to collect the information of the property according to their constraints.